CALL Communities and Culture – Short Papers From EUROCALL 2016 2016
DOI: 10.14705/rpnet.2016.eurocall2016.549
|View full text |Cite
|
Sign up to set email alerts
|

Japanese university students’ self-assessment and digital literacy test results

Abstract: Study abroad programs provide an opportunity for students to accelerate language learning and acquire cultural capital. Evaluations of returnees from study abroad programs however, have revealed that this is not always guaranteed. To promote a more positive academic and culturally-inclusive study abroad experience, one recommendation is for language teachers to focus on students' digital literacy. Given the reported levels of poor digital literacy among Japanese freshmen students, the researchers in this curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This resulted from the new policy that includes information computing technology in high school curriculum given by the Ministry of Education, Sports, Science and Technology (MEXT, 2011). However, Japanese students’ digital literacy is “falling behind other countries” (Cote and Milliner, 2016, p. 127). Results of a survey carried out by the Organisation for Economic Co-operation and Development (OECD) also demonstrates this.…”
Section: Japanese Students’ E-readinessmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted from the new policy that includes information computing technology in high school curriculum given by the Ministry of Education, Sports, Science and Technology (MEXT, 2011). However, Japanese students’ digital literacy is “falling behind other countries” (Cote and Milliner, 2016, p. 127). Results of a survey carried out by the Organisation for Economic Co-operation and Development (OECD) also demonstrates this.…”
Section: Japanese Students’ E-readinessmentioning
confidence: 99%
“…In other countries, the rate is higher than this, for example, Korea (63%), the USA (73%), the UK (78%) and Denmark (94%) (Maita, 2020). As Cote and Milliner (2016) state, “ICT utilisation in Japanese schools has not been advancing at rates similar to those in other industrialized nations” (p. 127). Gobel and Kano (2014) state that the lowest Japanese students’ computer proficiency and confidence in the OECD is due to “[a] lack of funds and modern equipment, minimal teacher training, as well as a lack of direction and vision from senior staff and school administrators” (p. 27).…”
Section: Japanese Students’ E-readinessmentioning
confidence: 99%
“…Although Japan is ranked among the top ten countries in terms of ICT access and usage (International Telecommunication Union, 2017), and most of the universities are equipped with highly designed CALL classrooms, Japanese students' digital literacy lags behind students of other advanced countries (Cote & Milliner, 2016). As stated in Cote and Milliner (2016), "The Organization for Economic Co-operation and Development (OECD, 2015) released a critical statement on the literacy of Japanese youth, noting that 25% (age 16-29) lack basic computer skills" (p. 127). Japanese students are assumed to be using ICT excessively in their everyday life, yet they hardly use their daily life ICT skills for using technology for learning (Cote & Milliner, 2016;Gobel & Kano, 2014;Lockley & Promnitz-Hayashi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As stated in Cote and Milliner (2016), "The Organization for Economic Co-operation and Development (OECD, 2015) released a critical statement on the literacy of Japanese youth, noting that 25% (age 16-29) lack basic computer skills" (p. 127). Japanese students are assumed to be using ICT excessively in their everyday life, yet they hardly use their daily life ICT skills for using technology for learning (Cote & Milliner, 2016;Gobel & Kano, 2014;Lockley & Promnitz-Hayashi, 2012). The lack of adequate ICT engagement in high schools results in students having low confidence for using digital technologies upon entering university, which affects their ability to independently use technology for language learning.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers at Tamagawa University Travis Cote and Brett Milliner published the study results on the students' digital literacy self-assessment conducted at Japanese universities. The scientists concluded that the respondents' self-assessment of their digital literacy is significantly lower than the real one (Cote & Milliner, 2016). presented the results of a study on the digital literacy of Indonesian women (Kurnia et al, 2020).…”
mentioning
confidence: 99%